Demutualization of Stock Exchanges: A Corporate Blessing in Disguise for Stock Market Growth. (July 2015) - Sial, Abdul Wahid; Talib, Nadeem; Ashkanani, Fayqa Abdullah; Alam, Muhammad Aftab
Abstract : Changes in ownership, governance, and objectives of stock exchanges significantly impact on stock market growth indicators such as number of listed companies, number of transactions in equity market, stock index, and market capitalization.